2012
DOI: 10.1002/ppul.22593
|View full text |Cite
|
Sign up to set email alerts
|

Sidestream microstream end tidal carbon dioxide measurements and blood gas correlations in neonatal intensive care unit

Abstract: ETCO(2) measurements using sidestream microstream technology in VLBW demonstrated that the correlation of ETCO(2) and PCO(2) was moderate, but the agreement was less than adequate (bias > 5 mmHg in all groups). The results improved with lower VD/VT, suggesting that sidestream capnography is more reliable in conditions of less severe lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
2
31
1
1
Order By: Relevance
“…[14] Similarly, other studies conducted in very low birth weight infants (VLBWI) with severe lung disease by sidestream–microstream capnograph revealed less reliable correlation and mean bias 13.5 ± 8.4 (95% agreement levels 3-29.9 mmHg). [1516] Among infants and children, our study found an excellent positive correlation between EtCO 2 and PaCO 2 , but severe lung disease as defined by P/F ratio <200 had a negative impact on this relationship. Similar to this, Macdonald[12] et al .…”
Section: Discussionmentioning
confidence: 62%
“…[14] Similarly, other studies conducted in very low birth weight infants (VLBWI) with severe lung disease by sidestream–microstream capnograph revealed less reliable correlation and mean bias 13.5 ± 8.4 (95% agreement levels 3-29.9 mmHg). [1516] Among infants and children, our study found an excellent positive correlation between EtCO 2 and PaCO 2 , but severe lung disease as defined by P/F ratio <200 had a negative impact on this relationship. Similar to this, Macdonald[12] et al .…”
Section: Discussionmentioning
confidence: 62%
“…Three studies report similar results of sidestream capnography in a neonatal population (8,11,12). Two other studies report better accuracy of sidestream measurement in a neonatal population (13,14).…”
Section: Discussionmentioning
confidence: 81%
“…This population suffers from problematic respiratory diffusion, ventilation of dead space, and shunting due to atelectasis. Earlier research showed that the Pa O2 /Fi O2 ratio and ventilation index had a significant influence on the relationship between Et CO2 and Pa CO2 measurements (1,2,(5)(6)(7)(8)(9). There are two methods of capnography.…”
mentioning
confidence: 99%
“…Recent studies on the accuracy of capnography in neonates show correlation coefficients between endtidal CO 2 (ET CO 2 ) and PaCO 2 between 0.72 and 0.95. However, this correlation decreases substantially in subgroups with a high-physiologic dead space ventilation (severe lung disease, very-low-birth-weight neonates), in which the difference between ET CO 2 and arterial measured PaCO 2 can increase to 17.8 AE 6.7 mmHg (57)(58)(59)(60). Although the ET CO 2 value is in general lower than the corresponding PaCO 2 value, in some patients, the ET CO 2 overestimates the PaCO 2 .…”
Section: Hypocapnia and The Brainmentioning
confidence: 99%